Measurement of Badminton Physical Tests on Students of Junior High School 2 Indaralaya Utara Using Outdor Laboratory - Ariansyah, Febri Rian; Hartati, Hartati; Victorian, Ahmad Richard (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
A fit physical condition is a state in which the body is able to carry out various activities to the fullest without experiencing excessive fatigue. Good physical condition for junior high school students is very important because it can support their achievements in both the academic and non-academic fields. Therefore the research aims to determine the physical condition of students in extra-curricular badminton at Junior Hight School Junior Hight School2 Indralaya Utara. This type of research is a descriptive quantitative research where researchers will find out the value of the results of a fitness test conducted by 20 students of Junior Hight School 2 Indralaya Utara. In this study the tests used to measure students' physical fitness were zig-zag running tests, push ups, sit ups, upright jumps and bleep tests. The data analysis used in this study is a descriptive percentage. The results obtained from the physical condition of the students of Junior Hight School2 Indralaya Utara, namely out of 20 students in total using the test norm reference, are as follows: for the Very Good category, the score is 55%, Good 35%, Enough 10, Less 0% and Very Less 0%. The total number in percentage is 100%. From the data obtained, it shows that the physical level of students at Junior Hight School2 Indralaya is quite good